2009
DOI: 10.1111/j.1754-9485.2009.02035.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intra‐arterial digital subtraction angiography using carbon dioxide by ‘home made’ delivery system and conventional iodinated contrast media in the evaluation of peripheral arterial occlusive disease of the lower limbs

Abstract: To prospectively compare the feasibility, safety and diagnostic role of carbon dioxide (CO(2)) digital subtraction angiography (DSA) using a 'home made' delivery system with iodinated contrast medium (ICM) DSA in the evaluation of peripheral arterial occlusive diseases (PAOD) of lower limbs. Twenty-one patients (27 limbs; all men; mean age, 47.6 years) who presented with PAOD of lower limbs underwent DSA using both intra-arterial CO(2) and ICM. Conventional ICM DSA was performed first and used as gold standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
0
23
1
1
Order By: Relevance
“…Fujihara et al reported an overall 17.3% rate (17 events out of 98 cases) of nonrenal events (limb pain/abdominal pain)—including two deaths attributable to CO 2 use . Kawasaki et al reported that 14.6% of patients undergoing CO 2 angiography complained of transient lower extremity pain, while Madhusudan reported this incidence to be 4.8% employing the use of a customized delivery system for intra‐arterial injections . The mechanisms underlying these effects in individual studies were not elucidated but likely involved either the vapor lock phenomenon or transient symptoms from blood displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Fujihara et al reported an overall 17.3% rate (17 events out of 98 cases) of nonrenal events (limb pain/abdominal pain)—including two deaths attributable to CO 2 use . Kawasaki et al reported that 14.6% of patients undergoing CO 2 angiography complained of transient lower extremity pain, while Madhusudan reported this incidence to be 4.8% employing the use of a customized delivery system for intra‐arterial injections . The mechanisms underlying these effects in individual studies were not elucidated but likely involved either the vapor lock phenomenon or transient symptoms from blood displacement.…”
Section: Discussionmentioning
confidence: 99%
“…It provides adequate imaging of the arteries of lower extremities, except for infrapopliteal segments. 13 Rolland et al reported that the imaging quality of CO2 arteriograms was comparable to the iodinated contrast media arteriograms from the pelvis in 93% and at the thigh in 74% of the 120 arteries studied. 15 To obtain fine images of CO2 arteriograms, we have to kept to a minimum all motion during image acquisition.…”
Section: Imaging Quality Of Carbon Dioxide Arteriogramsmentioning
confidence: 99%
“…Because the bag was used to transport the gas from the operating room to the DSA suite in this system, the procedures for preparing the system was complicated. 13 Unfortunately, the published CO2 delivery systems have been used only by a limited number of physicians and operators because of the complexity of the delivery system. Our delivery system is simpler and more user-friendly than the previously described published systems.…”
Section: Safety Of the Simple Homemade Carbon Dioxide Delivery Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…1 As Dr Mendes correctly concludes, our current method of aspirating CO2 has a higher probability of room air contamination as compared with methods of underwater aspiration. 2, 3 However, we have not experienced any complications related to air contamination in our study, which included 50 patients, of 70 cases.…”
mentioning
confidence: 99%